If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(4t + -4) + 2t = 7t + -3 Reorder the terms: -5(-4 + 4t) + 2t = 7t + -3 (-4 * -5 + 4t * -5) + 2t = 7t + -3 (20 + -20t) + 2t = 7t + -3 Combine like terms: -20t + 2t = -18t 20 + -18t = 7t + -3 Reorder the terms: 20 + -18t = -3 + 7t Solving 20 + -18t = -3 + 7t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-7t' to each side of the equation. 20 + -18t + -7t = -3 + 7t + -7t Combine like terms: -18t + -7t = -25t 20 + -25t = -3 + 7t + -7t Combine like terms: 7t + -7t = 0 20 + -25t = -3 + 0 20 + -25t = -3 Add '-20' to each side of the equation. 20 + -20 + -25t = -3 + -20 Combine like terms: 20 + -20 = 0 0 + -25t = -3 + -20 -25t = -3 + -20 Combine like terms: -3 + -20 = -23 -25t = -23 Divide each side by '-25'. t = 0.92 Simplifying t = 0.92
| -x+44= | | 67x+400=87x | | -2c+5= | | 10y-5x=45 | | 2(6m+2)= | | 15x+148=11x+160 | | 9m-6+1k=34 | | -22=x-9 | | X^2+20=6x^2 | | 15x+133=11x+189 | | 0=12x-12y-12 | | 18x+130=12x+169 | | x^2+y^2-14x+4y+49=0 | | X+5=2x+12 | | a/14=a-19 | | 13x+135=18x+135 | | 3x^2+10x-8=2x^2+5x-14 | | 3x^2+10x-8=2x^2+4 | | 9/14=a-19 | | 3(b-13)=9 | | 18x+133=14x+159 | | (4t-3t-6t)=1/t | | 18x+133=14x+149 | | 10z-30-4z=10(z-5)C | | 8+3s-7=9s+16-3s | | 18x+103=13x+164 | | 3(y+5)=2y-4+yD | | 3(y+5)=2y+15+yC | | 5x^2+12=-8 | | x^4-7x^2+10=f(x) | | 8x+55=2x+85 | | y=25x+-100 |